Popularising strawberry cultivation in Jammu and Kashmir - Ganai, N A; Rasool, Khalid; Ali, Angrej (Indian Horticulture, 2019)
Strawberry (Fragaria Ã— ananassa Duch.) is an important fruit crop of India and its commercial production is possible in temperate and sub-tropical areas of the country. Modern cultivated strawberry is an octaploid (2n=8x=56 chromosomes) hybrid species. It has become favourite fruit crop among the Indian growers near towns and cities, because of its remunerative prices and higher profitability, which has resulted a phenomenal increase in its area and production in the recent years. Many of the farmers are cultivating strawberries in Kashmir and are harvesting the bumper crop since past one decade. The farmers believe that the crop is better than other traditional crops grown. The farmers are very eager to go for strawberry plantation in their fields due to its good demand in the local market combined with its early maturing as it is available in the market during May and June. Moreover, the farmers are raising strawberry as an inter crop and are getting good dividends.